Analisis Penggunaan Metode Tilawati Dalam Mengoptimalkan Kemampuan Membaca Al-Quran Pada Siswa Kelas 7 Di MTS Muhammadiyah 1 Malang - Ummah, Munhidlatul; Mufidah, Vika Nurul (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2022)
The inability of students to read the Qur'an properly and correctly in accordance with the rules of recitation is caused by disorder or crowds when reading the Qur'an, causing students to be less focused in participating in learning. Therefore, this study aims to find out how the results of the analysis of the application of the tilawati method to Al-Qur'an reading subjects. The method in this study uses a qualitative method with a class action research type. The results showed that in the two cycles that had been carried out there was an increase in Al-Qur'an reading in MTS Muhammadiyah I Malang students, namely by 54% and 92%.